Sequential Trading with Coarse Contingencies - Sarah Auster; Jeremy Kettering; Asen Kochov (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
We consider a dynamic economy in which agents are initially unaware of some risks. As awareness of these risks emerges, markets re-open so agents can re-optimize and purchase insurance. An inefficiency may nonetheless arise as the cost of insurance is not spread over time. This "savings mistake" does not arise in two benchmark cases. In those, the ability to re-trade fully negates the initial misperception of risks. We also demonstrate the possibility of unexpected default. This arises when agents borrow "too much" and once perceptions change, there is no equilibrium price at which they can refinance their debt.
Keywords: 330; coarse perceptions; unforeseen risks; sequential trading; default